นิพนธ์ต้นฉบับ : ประสิทธิผลของการใช้แนวปฏิบัติทางคลินิกสำหรับการป้องกันภาวะอุณหภูมิ กายต่ำในผู้ป่วยที่ได้รับการผ่าตัดคลอดทางหน้าท้องและการระงับความรู้สึกโดย ฉีดยาชาเข้าช่องน้ำไขสันหลัง โรงพยาบาลมหาราชนครเชียงใหม่ - นฐธิกานตร์ เจริญรัตนเดชะกูล (Faculty of Medicine, Chiang Mai University, 2019)
Chiang Mai Medical Journal (Formerly Chiang Mai Medical Bulletin) is an official journal of the Faculty of Medicine, Chiang Mai University. It accepts original papers on clinical and experimental research that are pertinent in the biomedical sciences. The Journal is published 4 issues/year (i.e., Mar, Jun, Sep, and Dec).